ESTABLISHMENT OF PROFICIENT IN VITRO MASS MULTIPLICATION AND REGENERATION SYSTEM FOR ENHANCED PRODUCTION OF STEVIOSIDE AND REBAUDIOSIDE A IN STEVIA REBAUDIANA - M. B. Tufail; G. Mustafa; F. A. Joyia; Z. Mushtaq; Ghazala; M. S. Khan (Journal of Animal and Plant Sciences, 2019)
Stevia rebaudiana is not only a pivotal source of non-caloric sweetener but is also a medicinally important herb. Propagation through seed has certain limitations as it responds in particular environmental conditions and cannot tolerate temperature beyond 30oC. Keeping these limitations in mind, a proficient in vitro micro-propagation and regeneration system was established in this sweet herb to promote it as a non-caloric sweetener. In this experiment, various concentrations and combinations of growth regulators were tested to seek for the most responsive protocol for micro-propagation and regeneration. The best regeneration response was observed on MS medium containing Murashige and Skoog salts (4.33g/L), sucrose (30 g/L), 6-benzalamino purine (1.5 mg/L) and kinetin (0.5 mg/L) with maximum number of shoots (19.00± 0.57). Similarly, indole-3-butyric acid proved to be an appropriate growth regulator for root induction and proliferation. Rather differential role of IBA was observed as root number increased but root length decreased with increase in IBA concentration. The acclimatized plants in pots were tested for the production of non-caloric sweeteners (stevioside and rebaudioside A) through High Performance Liquid Chromatography (HPLC). Hence, we conclude that this protocol will prove a step forward in promoting availability of this non-caloric sweetener for diabetic patients.
Keywords: Micro-propagation; growth regulators; HPLC; qualitative analysis; stevioside; rebaudioside A